2012
DOI: 10.1515/humor-2012-0025
|View full text |Cite
|
Sign up to set email alerts
|

Humor use in power-differentiated interactions

Abstract: Humor serves a variety of functions in interpersonal communication, including the release of tension and the diffusion of conflict. Based on Dyadic Power Theory (Dunbar 2004; Dunbar and Abra 2010), it is predicted that interactants of equal power will use more humor and different types of humor than those either relatively high or low in power as compared to their partners. The present study analyzed experimentally manipulated problem-solving interactions between research participants (N = 150) and confederate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…Hay (2000) and Dunbar et al (2012) also found that a sharing type of humor (exchanged while sharing personal experiences or self-revealing stories) serves to create solidarity and is much more common among women than among men. Crawford and Gressley (1991) and Crawford (2003) also showed that the preferred type of humor among women is sharing funny, mundane, personal experiences from everyday life in order to create a "shared understanding of life's absurdities" (Crawford 2003(Crawford : 1421, while men's humor functions as a form of status competition.…”
Section: Discussionmentioning
confidence: 99%
“…Hay (2000) and Dunbar et al (2012) also found that a sharing type of humor (exchanged while sharing personal experiences or self-revealing stories) serves to create solidarity and is much more common among women than among men. Crawford and Gressley (1991) and Crawford (2003) also showed that the preferred type of humor among women is sharing funny, mundane, personal experiences from everyday life in order to create a "shared understanding of life's absurdities" (Crawford 2003(Crawford : 1421, while men's humor functions as a form of status competition.…”
Section: Discussionmentioning
confidence: 99%
“…Humour is commonly defined as the communication of multiple, incongruous meanings that are amusing in some manner (Dunbar, Banas, Rodrigues, Liu, & Abra, 2012;Martin, 2007). Humour theories can be classified into three groups: incongruity, superiority and relief theories.…”
Section: Humour and Children's Humourmentioning
confidence: 99%
“…In the future, longitudinal studies need to be conducted with existing long-term groups to capture the interplay between put-down humor and cohesion over time. Additional studies should also examine how group processes and the production of humor are associated (Dunbar et al 2012) and how the effects of humor play out in a work context (Van den Broeck et al 2012). Such studies can also help in formulating a richer theory about the effects of put-down and other forms of humor in groups.…”
Section: Limitations and Future Researchmentioning
confidence: 99%